The Role of Management and School in Organising Primary Students' Free Time - Karačić, Marija (Journal of Education Culture and Society, 2022)
Aim. The aim of the research is to determine what role management and schools play in the organisation of students” free time, and what activities it undertakes to educate for leisure time.Methods. This study used methods of theoretical analysis, survey research methods, and questionnaires, in which 1410 subjects such as principals, teachers, parents and students from 150 primary schools in Bosnia and Herzegowina (B&H) participated.Results. The results show that principals and teachers have positive attitudes about the rational use of students’ free time in order to prepare them  for continuing self-education with the use of various sources of knowledge.Conclusion. Conclusions show that for a better understanding of the role of school management it is necessary to do more research about this issue on the territory of B&H, because the proper organisation and implementation of students’ free time can be successful if all participants in education work together.Research restrictions. Since it is not possible to make comparison with results of the previous research on this topic on the territory of B&H,  the study compares results with results from other countries.Practical application. The practical goal is to examine the education and to increase the understanding and awareness of the free time of young people.Originality. This study is original and creative, and it contributes to better understanding of the role of management in leisure activities on students’ emotional, social, cognitive and work competencies.